TIKTOK: INOVASI MEDIA DIGITAL SEBAGAI ALTERNATIF PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI ERA MILENIAL - Wijaya, Asep (FAJAR Jurnal Pendidikan Islam, 2023)
The increase in TikTok social media users in Indonesia has created an excellent opportunity to take advantage of it, not only for entertainment but also as a medium in the learning process. This research aims to be able to take advantage of social media, namely the TikTok application to be used in learning Islamic religious education in this millennial era. the method used is a qualitative research method with a Library Research design. The data collection technique involves looking for relevant sources, both books and journals with national reputations, as for the analysis using content analysis (content analysis). The results of the study show that implementing the TikTok application in learning can be done in two ways, first: making the teacher the content creator himself, second: using videos from other content creators to make learning materials. The advantage of using the Tiktok application is that it can increase the teacher's creative spirit and the opportunity to earn income. Meanwhile, the drawbacks are, that there is no creative spirit, not everyone likes to play the TikTok application, different learning styles.